Development of nanoemulsion formulation loaded with Enteromorpha intestinalis extract: Characterization and evaluation for topical use - Shumaila Qadir; Shahlla Imam; Syed Abid Ali; Fatima Ramzan Ali; Wajiha Iffat; Rabia Ismail Yousuf; Rafia Usman; Shahana Wahid; Iqbal Azhar (PLoS ONE, 2026)
Enteromorpha intestinalis is a green seaweed enriched with diverse bioactive compounds that possess substantial pharmacological and biotechnological properties. Despite the focus on their therapeutic applications, research on the development of nano-formulations is limited. Therefore, this study aimed to develop an E. intestinalis (EI) extract-based nanoemulsion for topical use. Olive oil, Tween-80 (surfactant), and PEG-400 (co-surfactant) were selected for the formulation of the nanoemulsion. The Smix ratio was set to 1:1 using a pseudo-ternary phase diagram. Moreover, a design experiment ascertained the composition of the formulation, followed by physicochemical characterization. The optimal formulation, based on droplet size, was selected for further analysis. Stability studies, antioxidant and anti-inflammatory properties of selected nanoemulsion formulation were determined and acute dermal toxicity assay was also performed. The best formulation (F6) displayed a droplet size of 183.27 ± 20.04 nm, PDI of 0.6, and viscosity of 290 ± 5.77 m-Pa.S. The developed nanoemulsion exhibited good skin compatibility and a slightly acidic pH. Both the extract and nanoemulsion formulation exhibited concentration-dependent antioxidant activity. The nanoemulsion had a lower IC 50 value of 163.19 μg/mL, showing greater efficacy than the seaweed extract alone. Formulation (F6) also significantly (p < 0.05) inhibited paw volume (8–31%) compared to the control, while diclofenac sodium achieved a maximum inhibition of 41%. The designed formulation was stable, effective, and non-irritating demonstrating its potential topical application. This study presents, for the first time, a nanoemulsion formulation that incorporates E. intestinalis extract. This advancement paves the way for further in vivo studies to assess the efficacy and safety of this formulation for clinical applications.